Crystal structure of 3-[4-(1-methylethyl)phenyl]-1-(naphthalen-2-yl)prop-2-en-1-one - Sid Assia; Messai Amel; Ziani Nouara; Mokhtari Mahieddine; Lamara Kaddour (Acta Crystallographica Section E, 2014)
The title compound, C22H20O, was synthesized by reacting 4-isopropylbenzaldehyde with 2-acetonaphtone by aldolic condensation under Claisen–Schmidt conditions. The molecule consists of a naphthalene group and a benzene ring with a pendant isopropyl moiety, both rings bound by a propenone linker. The naphthalene ring system is almost planar [maximum deviation from the least-squares plane = 0.026 (10) Å] and subtends a dihedral angle of 52.31 (4)° with the benzene ring. The propenone linker, in turn, deviates slightly more from planarity [maximum deviation = 0.125 (18) Å] and has its least-squares plane oriented midway the former two, at 25.62 (6) and 28.02 (5)° from the naphthalene ring system and the benzene ring, respectively. Finally, the isopropyl group presents its CC2 plane almost perpendicular to the benzene ring, at 85.30 (4)°. No significant hydrogen bonding or π–π stacking interactions are found in the crystal structure.